(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This scientific article analyzes the role of Artificial Intelligence (AI) technologies in the educational process, their pedagogical effectiveness, and their integration into modern education systems. The study provides a scientific and theoretical justification for the impact of AI-based adaptive learning platforms, automated assessment systems, data analytics tools, and virtual assistants on the learning process. In particular, intelligent systems such as ChatGPT, developed by OpenAI, are highlighted for their ability to provide individualized learning approaches, foster independent learning skills, and support teachers’ professional activities. Additionally, the article addresses challenges associated with the use of AI technologies, including information security, data privacy, and algorithmic fairness. The findings of the study confirm that responsible and rational use of artificial intelligence is a key factor in enhancing education quality, optimizing the learning process, and accelerating digital transformation.